Analysis of genotype-environment interactions of silage maize cultivars under environmental trials (Bangladesh Journal of Botany, 2020)
To evaluate the adaptability and stability of silage maize cultivars and identify the representativeness and discrimination of each testing site, a two-year field research in a randomized complete block design (RCBD) with three replicates at 10 testing sites was conducted. An additive main effect and multiplicative interaction (AMMI) model and a genotype plus genotype environment interactions (GEI) biplot (referred to as GGE hereafter) were used to analyze the data. The two-year test revealed that four cultivars (Zhongdi 175 (ZD175), Qiushuo 008 (Q008), Hengyu 1587 (H1587), and Yayuqingzhu 8 (Y8) exhibited high yield and good stability, whereas two cultivars (Zhongbeiqingzhu 410 (Z410) and Fangyu 36 (F36) had low yield and poor stability. The comprehensive application of the AMMI model and the GGE biplot could accurately and intuitively evaluate the high yield, stability, and adaptability of each cultivar.